The Moderating Effect of Birth Satisfaction on the Correlation Between Mother-Infant Bonding and Psychological Resilience - Zeliha Özşahin; Çiğdem Karakayalı Ay; Esra Karataş Okyay (Genel Tıp Dergisi, 2023)
Objectives:This study was conducted to evaluate the moderator role of birth satisfaction in its correlation with mother-infant bonding and psychological resilience. Methods:This study was a cross-sectional study. The population of this study consisted of puerperal women who gave birth in a public hospital in Turkey. The sample size was calculated as at least 437 puerperal women and included 491 puerperal women in total. Personal Introduction Form, the Brief Resilience Scale (BRS), Mother to Infant Bonding Scale (MIBS), and Birth Satisfaction Scale–Short Form (BSS–Short) were used to collect data. Results:Mean age of puerperal women included in this study was 28.07±5.17. The mean BSS-Short total score was 20.35±6.07, the mean MIBS total score was 1.73±2.44, and the mean BRS total score was 19.18± 4.50. In this study, it was determined that the correlation between birth satisfaction and mother-infant bonding increased as the level of psychological resilience increased. In addition to this, the simple slope analysis revealed that the effect of psychological resilience on mother-infant bonding was not significant in cases where birth satisfaction was high(B=-0.22,p=0.10) and the effect of psychological resilience on mother-infant bonding was significant in cases where birth satisfaction was moderate(B=-0.44,p=0.001) and high(B=-.71,p=0.001). Conclusion:It was concluded that the strength of the correlation between psychological resilience and mother-infant binding increased in cases where birth satisfaction was high.